2008
DOI: 10.2190/ag.66.1.d
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Successful Aging and Serious Leisure

Abstract: The purpose of this qualitative study is to examine whether engagement in a serious leisure activity provided older adults opportunities for successful aging. Data were collected through in-depth interviews at shag dance festivals in North Myrtle Beach, South Carolina. To provide structure for the interview, a general interview guide consisting of open-ended questions was used. A total of 31 interviews were conducted with 25 individuals and 6 couples, between 60 and 82 years of age. During the analysis stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(65 citation statements)
references
References 28 publications
3
57
0
3
Order By: Relevance
“…Diverse groups of people have been the targets of research in serious leisure literature, as researchers have examined older golfers (Siegenthaler & O'Dell, 2003); people with disabilities (Patterson, 2000); runners (Major, 2001); master swimmers (Hastings, Kurth, Schloder, & Cyr, 1995); volunteers (Gravelle & Larocque, 2005); adventure tourists (Kane & Zink, 2004); and football fans (Gibson, Willming, & Holdnak, 2002). Some studies of serious leisure have investigated the behavior of older adults and discovered that it is conducive to their well-being (Brown, McGuire, & Voelkl, 2008;Siegenthaler & O'Dell, 2003). For example, in a study of older golfers by Siegenthaler and O'Dell, older adults who are seriously devoted to golf are able to appreciate the contribution of serious leisure to their well-being.…”
mentioning
confidence: 99%
“…Diverse groups of people have been the targets of research in serious leisure literature, as researchers have examined older golfers (Siegenthaler & O'Dell, 2003); people with disabilities (Patterson, 2000); runners (Major, 2001); master swimmers (Hastings, Kurth, Schloder, & Cyr, 1995); volunteers (Gravelle & Larocque, 2005); adventure tourists (Kane & Zink, 2004); and football fans (Gibson, Willming, & Holdnak, 2002). Some studies of serious leisure have investigated the behavior of older adults and discovered that it is conducive to their well-being (Brown, McGuire, & Voelkl, 2008;Siegenthaler & O'Dell, 2003). For example, in a study of older golfers by Siegenthaler and O'Dell, older adults who are seriously devoted to golf are able to appreciate the contribution of serious leisure to their well-being.…”
mentioning
confidence: 99%
“…In a study conducted by Heo et al (2013), level of involvement in serious leisure is positively associated with the life satisfaction and health in older adults. Brown et al (2008) also discovered a positive relationship between serious leisure participation and successful aging among shag dancers. Additionally, some studies Argyle, 1993, 1994;Cheng, 2010) showed that the people who engage in leisure activities at the serious level have more leisure satisfaction and happiness than the people who participate in nonserious leisure activities (cited in Liu, 2014).…”
Section: Research Significancementioning
confidence: 92%
“…Several studies (Brown et al, 2008;Cheng, 2010;Heo et al, 2010;Heo et al, 2013;Kim et al, 2011;Liu, 2014; Argyle, 1993, 1994;Siegenthaler and O'Dell, 2003;Silverstein and Parker, 2002) have found serious leisure activities contribute to the quality of life and leisure satisfaction of the people without disabilities. While the contribution of serious leisure participation on quality of life and leisure satisfaction is well documented for individuals without disabilities, serious leisure for the people with disabilities has been largely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…In many leisure activities, this development of close personal relationships and of feelings of community membership is not only a benefit, but often for purpose of engagement (Brown, McGuire and Voelkl, 2008). Several independent pilots stressed that the social aspect of piloting was very important to them.…”
Section: (Sheila Age 53)mentioning
confidence: 99%
“…The importance of friendship among others involved in a serious leisure emerged as a core category in previous studies of serious leisure (Brown, McGuire, and Voelkl, 2008;Gibson, Willming, and Holdnak, 2002;Hunt, 2008;Stalp, Radina, and Lynch, 2008;Stebbins, 1992). The social element enables women pilots to become a part of an exclusive community that connects other women pilots from all over the world.…”
Section: (Sheila Age 53)mentioning
confidence: 99%